(3UaI edMeI jQhjgG GdMcje GdaGVd SjO GdMceGA HWdjehS Yf OGfjGd GdfHi Ydjg GdSdGes
(3ChdgG (B:s
(3hVM dge GdJLGQH YdiWhd GdSfjf ef WdhYgG GdTMQi GdjeGfjg heG MOK ai GdSfjf YfO Mdhd GdbeQ ai GdHQhL GdBKfi YTQ hbJ WdhYgG s
(3BNQgG (B:s
(3hcPdc SGFQ GdHQhL GdebOe PcQgG hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B243 - (3U(B251s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B72 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2957(3)) s
Keywords: (3Gdadcs